BEYOND IDEOLOGY: AN EXPLORATORY CASE STUDY OF WOMEN’S DISENGAGEMENT PATHWAYS FROM TRANSNATIONAL TERRORIST NETWORKS IN INDONESIA - Machya Astuti Dewi; Melaty Anggraini; Iva Rachmawati; Herlina Jayadianti (Indonesian Association for International Relations, 2026)
This study analyses factors influencing the disengagement of Indonesian women from transnational ISIS-affiliated networks. Utilizing the Attitudes-Behaviors Corrective (ABC) Model and gendered push-pull theory, this study presents a qualitative case study of three former ISIS sympathizers through semi-structured interviews. The research identifies three disengagement pathways: (1) relation-ideology disengagement through a partner with shared experiences; (2) behavioral disengagement via vocational training in prison and humane treatment from officers; and (3) religious interpretation disengagement through self-directed pragmatic accommodation. Findings show that women's disengagement is more relationally and practically oriented rather than rooted in organizational or ideological motivations, highlighting that their departure from these networks is not solely ideology-driven.